KARAKTERISASI ENZIM XILANASE DARI ISOLAT BACILLUS SP. UJ131 DI HUTAN MANGROVE MARGASARI LAMPUNG TIMUR SEBAGAI KANDIDAT PROBIOTIK - Sumardi, Sumardi; Farisi, Salman; Ekowati, Christina Nugroho; Hairisah, Suminta Frida (Indonesian Institute of Sciences, 2019)
Characterization of Xilanase Enzyme by Bacillus sp. UJ131 A Probiotic Candidate from the Mangrove of Margasari, East Lampung. Mangrove are known to have high biodiversity as a potential location for exploration of enzyme-producing bacteria, one of which is the xylanase enzyme. Xylanase is an enzyme that hydrolyzes the xylan-rich hemicellulose substrate. This research aims to produce and know the character of xylanase enzyme by Bacillus sp. UJ131 isolate which was isolated from the oriental shrimp in Margasari mangrove forest of East Lampung. Xylanase enzymes are produced from the bacteria by growing them in sea water complete (SWC) broth containing xylan beechwood. Characterization xylanase enzyme consist of pH, temperature, and metal ions. The results showed that xylanase had an optimal time of 18 hours with xylanase activity of 0.18 U/ml, and optimally at pH 6 and temperature 70°C. The addition of Mn2+ and Ca2+ ions increase enzyme activity, but Fe3+, Cu2+ and Mg2+ ions decrease xylanase enzyme activity. At a maximum reaction speed of 0.25 U/ml, the xylanase enzyme can produce 1.30 ?M xylose per minute